The impact of utilizing UHPFRC in beam-column joints with different patterns of transverse reinforcement - Ayman Abdo; Heba A. Mohamed; Talaat Ryad; Sayed Ahmed (Fracture and Structural Integrity)
This research studies and assesses the possibility of employing UHPFRC in exterior beam-column joints (BCJs). Eight specimens with various concrete material characteristics and steel reinforcing details are cast and examined under repeated loads. Normal concrete with seismic reinforcing details is used as a control specimen. For certain specimens, UHPC, UHPFRC with 1% steel fiber, and UHPFRC with 2% steel fiber are poured into all BCJs, and others are poured into the critical zone only. The consequences of removing stirrups from the joint were studied. All specimens' crack patterns, hysteresis and envelope curves, ductility factor, stiffness degradation‎, and energy dissipation are assessed and corresponded to the control sample. The results demonstrate that  UHPFRC strengthened the joint, prevented crack development and extension and the shear failure in the joint, and formed the plastic hinge in the beams. UHPFRC outperforms normal concrete with seismic reinforcing details and UHPC without steel fiber in bearing capacity, ductility, stiffness, and energy dissipation. UHPFRC with 1% steel fiber enhanced joint behavior, while UHPFRC with 2% steel fiber was better. Casting the whole sample with UHPFRC achieved very little improvement. The presence of stirrups in the UHPFRC beam-column joint has little effect on its properties. It is more economical to casting UHPFRC in the joint zone only and reduce or eliminate these stirrups in the case of UHPFRC